Xanthogranulomatous pyelonephritis presenting as a pseudotumour in a 5-year-old boy. (12th December 2012) - Berenguer, Alberto; Pilar, Carla; Smit, Michelle; Nunes, José Luis
Abstract : Xanthogranulomatous pyelonephritis (XGPN) is a rare, severe and atypical form of chronic pyelonephritis. It is characterised by destruction of the renal parenchyma and replacement with a chronic inflammatory infiltrate and lipid-laden macrophages resulting in a non-functional kidney. The authors report a case of a 5-year-old boy presented with a history of abdominal pain, malaise, anorexia and weight loss for 2 months. Physical examination revealed a large flank mass and the child was directed to the oncology unit on suspicion of renal tumour. Based on clinical examination and imaging, the presumptive diagnosis of XGPN of the left kidney was made. A left transperitoneal nephrectomy was performed and the histology confirmed the diagnosis. Although rare, XGPN is a clinically important entity that should be considered in the differential diagnosis of an atypical-appearance renal mass in paediatric age.